ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP KELAS VIII DALAM MENYELESAIKAN SOAL-SOAL TEOREMA PYTHAGORAS - Sudrajat Sudrajat (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This research aims to describe the mathematical communication skills in writing of junior high school students in grade VIII in solving the problems of Theorem Pythagoras. The method used in this study is a qualitative descriptive method.   The subjects of this study numbered 31 students and were categorized in groups of very high, high, medium, low and very low female students. The results showed that students who had mathematical communication skills in a very high group were students who were very able to meet the four indicators tested with an average percentage of 83%. The mathematical communication skills of students in the high group are students who are able to meet the four indicators tested with an average total percentage of 70%. The mathematical communication skills of students in the moderate group are students who are sufficiently able to meet the four indicators tested with an average total percentage of 51%. The mathematical communication skills of students in the lower group were students who were less able to meet the four indicators tested with an average total percentage of 32%. The mathematical communication skills of students in the very low group were students who had not been able to meet the four indicators tested with an average total percentage of 17%.